Predicting water absorption of wheat flour using high shear-based GlutoPeak test. (July 2017) - Fu, Bin Xiao; Wang, Kun; Dupuis, Brigitte
Abstract: Selection for water absorption, a fundamental wheat quality parameter, has been a challenge in wheat breeding programs due to limited wheat materials available for milling and consequent time-consuming farinograph test. Hence, a high shear-based method, which requires 8 g of flour and less than 10 min per test, was proposed to predict flour water absorption using the Brabender GlutoPeak instrument. Highly significant positive linear relationship (r 2  = 0.97) was found between GlutoPeak maximum torque and farinograph water absorption for 83 flour samples prepared with Bühler test mill from wheat lines under evaluation in the Canadian wheat variety registration trials. Similar strong correlation (r 2  = 0.96) was obtained from flours (n = 63) prepared with Quadrumat Junior laboratory mill using small amount of wheat. Flour prepared either with Bühler test mill or Quadrumat Junior mill can be used for predicting water absorption effectively. GlutoPeak maximum torque was found to be independent of dough strength (r 2  = 0.02) as measured by extensigraph. GlutoPeak test can be a powerful tool for rapid and reliable prediction of water absorption of wheat flour. Highlights: Flour water absorption can be accurately predicted with GlutoPeak maximum torque. GlutoPeak maximum torque was independent of dough strength. GlutoPeak requires only 8 g of flour and less than 10 min for each test. Flour from small-scale lab mill can be used for predicting water absorption.